2011
DOI: 10.1016/j.ijdevneu.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of neuronal and glial populations of the visual system during zebrafish lifespan

Abstract: During visual system morphogenesis, several cell populations arise at different time points correlating with the expression of specific molecular markers We have analysed the distribution pattern of three molecular markers (zn-1, calretinin and glial fibrillary acidic protein) which are involved in the development of zebrafish retina and optic tectum. zn-1 is a neural antigen expressed in the developing zebrafish central nervous system. Calretinin is the first calcium-binding protein expressed in the central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
0
6
0
4
Order By: Relevance
“…Here we have CR in the proximal layer, but as the distal layer appears uniformly stained for CR by confocal microscopy, we infer that the GFAP‐containing supporting cells may also contain CR. Various calcium‐binding proteins are frequently found to coexist in the vertebrate nervous system (see, for example: Caceres, Bender, Snavely, Rebhun, & Steward, ; Castagna, Viglietti‐Panzica, & Carlo Panzica, ; Manso, Becerra, Becerra, & Anadón, ; Schmidt‐Kastner & Szymas, ), as well as in the retina (Arenzana et al, ; Kondo et al,; Linser & Moscona, ; Schnitzer, ; Tabuchi & Kirsch, ; Terenghi, Cocchia, Michetti, Diani, Peterson, Cole, & Polak, ; Weruaga, Velasco, Briñón, Arévalo, Aijón, & Alonso, ). Our study is the first to suggest that CR may coexist with GFAP in the cephalopod retina glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have CR in the proximal layer, but as the distal layer appears uniformly stained for CR by confocal microscopy, we infer that the GFAP‐containing supporting cells may also contain CR. Various calcium‐binding proteins are frequently found to coexist in the vertebrate nervous system (see, for example: Caceres, Bender, Snavely, Rebhun, & Steward, ; Castagna, Viglietti‐Panzica, & Carlo Panzica, ; Manso, Becerra, Becerra, & Anadón, ; Schmidt‐Kastner & Szymas, ), as well as in the retina (Arenzana et al, ; Kondo et al,; Linser & Moscona, ; Schnitzer, ; Tabuchi & Kirsch, ; Terenghi, Cocchia, Michetti, Diani, Peterson, Cole, & Polak, ; Weruaga, Velasco, Briñón, Arévalo, Aijón, & Alonso, ). Our study is the first to suggest that CR may coexist with GFAP in the cephalopod retina glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that major zebrafish tissues and organs share many features with human counterparts at the anatomical, physiological and molecular levels, including brain, heart, muscles, kidney, and liver [9,10,11,12,13]. Even though most of the toxicological tests are performed on zebrafish embryos, the adult organism is also an excellent model to study toxicants influence on mature organism physiology, lifespan, disease and behavior [14,15,16,17]. It has been demonstrated that adult zebrafish is a suitable model to measure the effects of the exposure to variety of chemicals including therapeutic drugs and environmental toxicants [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…En peces hay expresión de calretinina 1. Introducción en el techoóptico de tenca (Arévalo et al, 1995) y del pez cebra (Castro et al, 2006;Arenzana et al, 2011), en elárea preóptica de la trucha (Castro et al, 2003) y en las fibras del sistema electrosensorial en peces mormíridos (Friedman y Kawasaki, 1997). En la retina del pez cebra se empieza a expresar a las 48 horas post fecundación, con un marcaje correspondiente a células amacrinas (Arenzana et al, 2011).…”
Section: Calretininaunclassified
“…Introducción en el techoóptico de tenca (Arévalo et al, 1995) y del pez cebra (Castro et al, 2006;Arenzana et al, 2011), en elárea preóptica de la trucha (Castro et al, 2003) y en las fibras del sistema electrosensorial en peces mormíridos (Friedman y Kawasaki, 1997). En la retina del pez cebra se empieza a expresar a las 48 horas post fecundación, con un marcaje correspondiente a células amacrinas (Arenzana et al, 2011). Posteriormente, se expresa en las células ganglionares y en amacrinas de la CNI, y esta distribución se mantiene hasta la edad adulta (Yazulla y Studholme, 2001;García-Crespo y Vecino, 2004;Arenzana et al, 2011;Cederlund et al, 2011).…”
Section: Calretininaunclassified
See 1 more Smart Citation